Potret Ashabul Ukhdud dalam Al-Qur’an (Kajian Kitab Shafwah At-Tafasir) - Aditya Rizki Ramadhan; Septiawadi Kari Mukmin; Muhammad Tauhid (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2026)
This study examines Muhammad Ali Ash-Shabuni's interpretation of the story of Ashab al-Ukhdud in QS. Al-Buruj verses 4–11 as presented in his exegesis Shafwah at-Tafasir focusing on the meaning of